Gender-Based Variances in Student Interest and Commitment to Mathematical Tasks in Secondary Schools in Bamenda Municipality - Nkepah, Beyoh Dieudone (EDUPEDIA Publisher, 2025)
This study investigates gender-based differences in secondary school students' interest in and commitment to mathematical tasks at three educational stages in Bamenda Municipality, Cameroon. Recognising the critical role of mathematics in academic and career success, the research aims to trace how gender influences interest and engagement throughout secondary education. Two specific objectives gave focus to the study. Employing a cross-sectional developmental research design, data were collected from 375 students across Forms 1, 4, and 6 using a self-designed student questionnaire validated by experts, which assessed students’ interests and commitment to mathematical tasks. A Cronbach's alpha reliability coefficient of 0.89 assured the reliability of the instrument. Data were analysed using frequency counts, means, and ANOVA. Findings reveal that male students exhibit higher overall interest and commitment levels compared to female students, with significant fluctuations noted at various educational stages. In particular, female students show increased variability in interest, especially in early forms, and a pronounced decline in commitment by Form 4. Recommendations emphasise targeted interventions, inclusive teaching strategies, and active efforts to challenge gender stereotypes in mathematics education. By addressing these disparities, the research aims to inform practices that enhance student engagement and foster a more equitable learning environment within the mathematics classroom.